ответ: x=(1+1/y²)/2.
Пошаговое объяснение:
Выразите переменную х через переменную у из формулы
у = 1/(√2x-1).
y*√(2x-1)=1;
y²*(2x-1)=1;
2x-1=1/y²;
2x=1+1/y²;
x=(1+1/y²)/2.
Вариант 1 (если под корнем 2x-1):
---------------------------------------
Вариант второй (если под корнем 2x):
ответ: x=(1+1/y²)/2.
Пошаговое объяснение:
Выразите переменную х через переменную у из формулы
у = 1/(√2x-1).
y*√(2x-1)=1;
y²*(2x-1)=1;
2x-1=1/y²;
2x=1+1/y²;
x=(1+1/y²)/2.
Вариант 1 (если под корнем 2x-1):
---------------------------------------
Вариант второй (если под корнем 2x):